Development and Validation of a Simple and Selective Analytical HPLC Method for the Quantification of Oxaliplatin - Breno Noronha Matos; Paula Martins de Oliveira; Thaiene Avila Reis; Taís Gratieri; Marcílio Cunha-Filho; Guilherme Martins Gelfuso (Journal of Chemistry)
Considering that currently published oxaliplatin (OXPt) analytical methods require complex procedures and equipment, the objective of this paper was to present the validation of a simple, rapid, precise, and specific isocratic HPLC method for quantification of OXPt. Such method will be essential during the future development of innovative, topical drug formulations for the treatment of mucosal and skin cancers. Validated method demonstrated OXPt separation without interference from the solvents or polymers with the most relevance for developing of bioadhesive pharmaceutical drug carries (chitosan and poloxamer). Method was linear (r>0.999) over studied OXPt concentration range (0.5–15.0 µg/mL) with acceptable precision and accuracy. Limit of detection (LOD) and limit of quantification (LOQ) were 0.099 µg/mL and 0.331 µg/mL, respectively.